(untitled) (NAU Journal of Library and Information Science, 2025)
This work is focused on establishing how digitization of library information materials affects the research productivity of Librarians in Nigeria. The descriptive survey research design was adopted for the study and the purposive sampling technique was employed in selecting 20 libraries that have digitized their information resources. Ten librarians, each from the universities were randomly selected for the study, making the sample size 200. Self-constructed questionnaire was the instrument used for data collection. Data collected was analyzed using SPSS software. The outcome revealed that the types of information resources digitized by the libraries include theses and dissertations, research works published in local journals, conference papers, and inaugural lectures. Opportunities presented by digitization that impact the research productivity include; enhanced access to existing local scholarly works, giving visibility to individual and institutional research output, making researchers discoverable, and exposing them to the knowledge of other researchers in their areas of interest for collaboration purposes, etc. The perceived impacts of digitization on the research productivity of librarians are; enhanced quality of research, enhanced research output, high citation impacts, created room for multi-disciplinary, national, and international collaborations, and made them visible to grantors and funding bodies. The major challenges hindering the effective utilization of these resources include; irregular Internet access, limited awareness of the availability of the resources, infrastructure limitations, and erratic power supply.